(untitled) (African Journal of Science, Technology and Social Sciences, 2025)
Safe disposal of faecal sludge remains a critical challenge in developing countries due to presence of harmful pathogens and odours. Current treatment methods are often inaccessible, ineffective, or costly, causing health and environmental risks. This study aimed to evaluate cabbage waste-derived lactic acid from fermentation of selected vegetable wastes for faecal sludge treatment as a low-cost and sustainable solution for faecal sludge management. Tomato, cabbage, and carrot wastes were fermented for six days at 37 °C with daily monitoring of pH and lactic acid concentrations. Four reactors with faecal sludge-to-lactic acid ratios of 1:1, 1:0.5, 1:0.35, v/v, and a control were set up and monitored for Escherichia coli, odour, total solids, and volatile solids reduction over 16 days. Cabbage-derived lactic acid was selected because the retention factor (Rf) was similar to the standard with no interfering organic acids. Reactor 1:1 eliminated E. coli within four days, achieving zero cfu/mL. TS decreased from 18.5 g/L to 14.5 g/L, while VS declined from 17.7 g/L to 7.6 g/L and 6.3 g/L in the 1:0.5 and 1:0.35 reactors, respectively. Odour reduction was also highest in this reactor, with a Threshold Odour Number (TON) of 7.3 compared to 25 in the control. These findings show that cabbage vegetable wastes can produce lactic acid that can lead to total E. coli elimination and significant odour elimination in faecal sludge. Studies should be carried out to explore feasibility of scaling up this method.